The Perspective of Laboratory High School Students on Tone Indicators - Michelle Aile A. Akiatan; Julius Ceasar P. Diamante; Jynaine Viel R. Mamada; Mark Christian G. Puedan; Amera C. Malaco (Indonesian Journal of Community and Special Needs Education, 2021)
This study’s purpose is to describe the importance of tone indicators in computer-mediated communication through gathering the opinions of high school students. This study employed a generic qualitative approach that allowed us to comprehend five students' perspectives on tone indicators. A thematic analysis helped us to identify significant statements, generate initial themes, formulate, and name relevant themes. The results showed that the participants of the study are not fully aware of tone indicators. In fact, the tone indicators are important, especially facing the problems and applying for facing special needs people. Their narratives indicate that misidentified tones of messages stimulate preconceptions to form in the minds of virtual readers, leading to miscommunication. The students expressed relief, enlightenment, and approval upon the introduction and application of tone indicators. They described the roles of tone indicators as tools to make messages clear. Therefore, tone indicators hold relevance in computer-mediated communication. This study promotes tone indicators awareness and tranquility in online communication.